Metabolomic profiling reveals novel biomarkers and therapeutic targets in Legg-Calvé-Perthes disease: a comprehensive analysis of peripheral blood and endothelial function - Zi, Shaoneng; Wang, Chengyong; Zhang, Tong; Lv, Qian; Wan, Zhiying; He, Pengju; Hang, Yong; Xu, Yongqing (Frontiers in Physiology, 2025)
IntroductionLegg-Calvé-Perthes disease (LCPD) is juvenile idiopathic femoral head avascular necrosis with unclear pathophysiology. We aimed to identify circulating metabolic biomarkers and clarify the roles of peripheral inflammation and vascular/endothelial dysfunction in LCPD, and to evaluate the protective potential of 3-ketoglucose (3-KG) and sanguinarine (SANG).MethodsPeripheral blood from children with LCPD (n=36) and healthy controls (n=6) underwent untargeted LC-MS metabolomics with differential and pathway analyses. Candidate metabolites (3-KG, SANG) were tested in LPS-challenged HUVECs for effects on viability, ROS, IL-1β/IL-6/TNF-α, and NF-κB/eNOS/VCAM-1 (RNA-seq, qPCR, Western blot, immunofluorescence). In vivo validation used a steroid/LPS-induced rat model of femoral head osteonecrosis assessing histology, adipogenesis, serum ALP/TG, and Nos3/Vcam1/Nfkb1 expression.ResultsThirty-eight metabolites differed significantly between LCPD and controls; 3-KG and SANG were upregulated, whereas several metabolites including N-methyl-D-aspartate were downregulated, mapping to inflammatory and oxidative-stress pathways. Both 3-KG and SANG dose-dependently mitigated LPS-induced HUVEC injury by restoring viability, lowering ROS and pro-inflammatory cytokines, and normalizing NF-κB/eNOS/VCAM-1 at mRNA and protein levels, with SANG showing greater potency. In rats, both compounds ameliorated bone loss and adipogenesis, increased ALP, reduced TG, and reversed MPS-induced changes in Nos3, Vcam1 and Nfkb1.DiscussionThis work defines a peripheral “metabolomic fingerprint” of LCPD and links systemic metabolic alterations to endothelial inflammation/dysfunction. 3-KG and SANG exhibit endothelial-protective activity in vitro and in vivo, supporting their promise as diagnostic biomarkers and therapeutic candidates. Larger, longitudinal cohorts are needed to validate these signatures and clarify stage-specific dynamics.